2020
DOI: 10.1177/0022343320929744
|View full text |Cite
|
Sign up to set email alerts
|

Commander–community ties after civil war

Abstract: Ex-rebel military commanders play a central role in peacebuilding after civil war. Yet the influence and mobilization power of these actors is not uniform: in some areas commanders retain strong ties to civilian populations after war’s end, while in other areas such ties wither away. This article analyses a novel dataset of former rebel-occupied localities in Côte d’Ivoire to investigate why commander–community linkages endure or decline after post-conflict transitions. The findings support a theory of politic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…For example, Kubota (2017) argues that governance by the Liberation Tigers of Tamil Eelan (LTTE) in Sri Lanka supplanted and co-opted state institutions, creating impediments to citizen trust and identification with the post-conflict government. Martin et al (2021a) and Martin (2021) similarly found that many rebel-occupied communities in Côte d'Ivoire continued to rely on ex-rebel actors for informal services and protection, crowding out the role of redeployed police forces. Rebel rule can also bolster community-based institutions and patterns of local collective action in response to service shortfalls (Barter, 2016;Mampilly, 2011;Wood, 2008).…”
Section: Motivation and Theorymentioning
confidence: 99%
“…For example, Kubota (2017) argues that governance by the Liberation Tigers of Tamil Eelan (LTTE) in Sri Lanka supplanted and co-opted state institutions, creating impediments to citizen trust and identification with the post-conflict government. Martin et al (2021a) and Martin (2021) similarly found that many rebel-occupied communities in Côte d'Ivoire continued to rely on ex-rebel actors for informal services and protection, crowding out the role of redeployed police forces. Rebel rule can also bolster community-based institutions and patterns of local collective action in response to service shortfalls (Barter, 2016;Mampilly, 2011;Wood, 2008).…”
Section: Motivation and Theorymentioning
confidence: 99%
“…Kubota (2017) shows that civilian identity (Tamil versus Sri Lankan) in northern and eastern areas of Sri Lanka is considerably shaped by how local populations perceive the legitimacy of state-like functions performed by the LTTE during the war. Improved legitimacy and capacity by armed groups may also ensure that civilians do not leave recently controlled territories, as Revkin (2021) shows for the case of the Islamic State in Mosul, and may also strengthen ties between armed group commanders and local communities in the post-war period (Martin 2021). Perceptions of legitimacy about the state-like roles of armed groups during wartime are important also because they define state-military-citizen relations in the post-war period.…”
Section: Legitimacy and Compliancementioning
confidence: 99%
“…The civil war reached a stalemate in mid-2003, which led to the establishment of a UNsupervised demilitarised zone that left 60% of the country under rebel control. 52 Following a period of 'no war, no peace', the civil war ended in massive bloodshed when the 2010 presidential election triggered masselectoral violence and the FN captured the economic capital Abidjan. 53 State-insurgent cooperation on rebel governance in northern Côte d'Ivoire started in 2003 and deepened incrementally.…”
Section: State-insurgent Cooperation In Côte D'ivoire (2002-2011)mentioning
confidence: 99%